PENGEMBANGAN MODEL PEMBERDAYAAN KELUARGA BERBASIS KONEKTIVITAS SOSIAL UNTUK PENCEGAHAN ISOLASI SOSIAL DAN PENINGKATAN KESEHATAN IBU DAN ANAK DI KOTA MAKASSAR - Rusni Mato (Jurnal Multidisipliner Kapalamada, 2026)
Social isolation among pregnant and postpartum women is a significant risk factor affecting maternal and child health (MCH), particularly in urban settings. This study aimed to develop and validate the Family Empowerment-Based Social Connectedness Model for Maternal and Child Health (FESCMCH) in Makassar City, Indonesia. A sequential exploratory mixed-methods design was employed. The qualitative phase involved 40 participants, including pregnant women, postpartum mothers, husbands, midwives, and community leaders. The quantitative phase recruited 300 mothers through stratified random sampling and analyzed the data using Structural Equation Modelling (SEM). The findings identified six core domains of social connectedness: husband involvement, extended family support, community cohesion, peer social networks, digital connectedness, and healthcare provider engagement. SEM results demonstrated that social connectedness significantly reduced social isolation and improved maternal and child health outcomes. The FESCMCH model was found to be valid and has strong potential for integration into family- and community-based maternal and child health services.